Examining the effects of learner-learner interactions on satisfaction and learning in an online undergraduate course. (December 2017) - Kurucay, Murat; Inan, Fethi A.
Abstract: The purpose of this study was to investigate the effects of learner-learner interactions on students' perceived learning, achievement, and satisfaction in an online undergraduate course. A quasi-experimental research design was conducted with 77 students registered into an online course. Two sections of the course were randomly assigned to control and treatment conditions. While students in the control group completed course assignments individually, students in the treatment group completed the assignments in small groups. The results of the study revealed that learner-learner interaction has a significant effect on students' achievement in an online course. Students working collaboratively achieved significantly higher than those working individually. Furthermore, students' perceptions of online collaboration increased after being involved in online group activities. Highlights: Learner-learner interaction does not impact student satisfaction in an online course. Interaction among learners significantly impacts student achievement in an online course. Peer contribution in group activities and students' satisfaction in an online course are significantly correlated. Students' perceptions of online collaboration improved after being involved in online group activities.